2016
DOI: 10.3109/02713683.2016.1143014
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of CTGF in the Human Eye

Abstract: CTGF was detected in various structures of the human eye. Since CTGF has been also described in aqueous humor, the identified structures might be the sources of CTGF in the aqueous humor. By means of aqueous flow, CTGF is transported into the trabecular meshwork, where it could change outflow facility and therefore affecting IOP homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…It was reported to induce the angio-fibrotic switch in diabetic retinopathy and to be involved in remodeling of the extracellular matrix in glaucoma. 88 90 …”
Section: Discussionmentioning
confidence: 99%
“…It was reported to induce the angio-fibrotic switch in diabetic retinopathy and to be involved in remodeling of the extracellular matrix in glaucoma. 88 90 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CTGF was also demonstrated as the matricellular proteins in glaucoma, which plays a role in fibrosis and increased extracellular matrix deposition . CTGF might be relevant for the development of elevated IOP, which is considered as a high‐risk factor in glaucoma pathogenesis . These results indicated high‐risk genes were key regulators in pathogenesis of glaucoma.…”
Section: Resultsmentioning
confidence: 89%
“…16 CTGF might be relevant for the development of elevated IOP, which is considered as a high-risk factor in glaucoma pathogenesis. 17 These results indicated high-risk genes were key regulators in pathogenesis of glaucoma.…”
Section: Identification Of Differentially Expressed Genesmentioning
confidence: 93%
“…However, previous studies have reported high intra-and inter-observer repeatability (19). Although we excluded patients with systemic hypertension, the absence of diastolic blood pressure measurements is another limitation of our study (20).…”
Section: Discussionmentioning
confidence: 90%